PANDANGAN SAINS TERHADAP HARAMNYA LEMAK BABI - Lubis, Lelya Hilda (IAIN PADANGSIDIMPUAN, 2013)
AbstractAl-Quran and Hadis relied upon by Muslims to determine something of foods including halal or haram. The term halal and haram are both derived from Arabic, meaning lawful or permitted justified, while haram means not permitted or prohibited. Pigs are clear keharamannya for Muslims either fat or part resulting from an animal. Prohibition of pork has been scientifically proven / science, so that we as Muslims must eat halal food anymore either (thayyib). Key words: science, haram, halal, lard